PROSSEIA-VR: training in the virtual environments - Grave, Luís (2012)
The Virtual Reality (VR) field can provide a wide variety of industrial applications. We can find several examples in the automobile industry, where VR is used for tasks like design, wind tunnel simulators, assemble/disassemble, etc. However, all these applications are designed to be used by VR experts,or well trained personnel. This happens because the VR devices and the VR interaction metaphors are not yet well developed to fulfil the needs of an inexperienced user, like robustness, failure recovery, easiness of use. All these aspects have to be resolved before an inexperienced user can effectively use such a system. The article reports about a two years CCG's industrial project aimet at solving, at least partially, this problem, targeting the training on wire twist assembly for the automobile industry.